Content Analysis on Potential Character Inclusion in Listening I Course Syllabus and Materials - Hidayah Nor Nor (Institut Agama Islam Negeri Palopo, 2019)
: The development of programs of study, learning and teaching resources, lesson plans and assessment of students, and even teacher education are all based on curriculum. It is also related to the integration of character education in the learning process carried out from the planning, implementation, and evaluation of learning in all subjects and it can be adopted in making lesson planning (syllabus, lesson plans and teaching materials). Since character education has recently become an important issue in the Indonesian education system, this research examines the potential incorporation of the character education in Listening 1 course syllabus and materials by doing content analysis. The findings reveal that there are 18 characters of education that can be applied in the syllabus, they are Caring and Compassionate, Creative, Curious, Democratic, Discipline, Empathy, Honest, Inclusion/Communicative, Independent, Love Peace, Love Reading, Love the Nation, Nationalistic, Religious, Responsible, Sportive and Respectful, Tolerant, and Work hard. Those characters are incorporated to the 10 topics (Meeting people for the first time, Families, Numbers, Let’s eat, Free time, Gifts, Part time jobs, Celebration, Invention, and Folktales) and also include in Introduction, Self Study, Expansion, Middle test and Final Test of Listening 1 course materials.